Advances in Islamic finance, marketing, and management : an Asian perspective - Mutum, Dilip S.; Butt, Mohammad Mohsin; Rashid, Mamunur (Emerald Group Publishing Limited, 2016)
Demonstrating high quality theoretical and empirical findings in the areas of Islamic finance, banking, entrepreneurship, insurance, capital market, Islamic leadership, and Halal marketing, this new work includes topics on consumer perception, services orientation, new product development, risk management, industry readiness for better customer satisfaction, and policy issues coupling strategy and best practices. Of interest to both academics and practitioners who assist in making Shariah-centric strategies, this work is particularly important as Asia holds a major percentage of Islamic assets in South Asia, Southeast Asia, and the Middle East, with new opportunities opening in Central Asia.